Pathophysiology, causes and pharmacological study of arterial thrombosis - G. SUDHAKARA RAO; G.SANDEEP KUMAR; PRASANTHI EVANGELIN (International Journal of Pharma and Bio Sciences, 2017)
Arterial thrombosis is the formation of blood clots in the deep veins. It commonly affects the deep leg veins or the deep veins of the pelvis. It is a potentially dangerous condition that can lead to preventable morbidity and mortality. Arterial thrombosis affects 0.1% of persons per year. The approach to making a diagnosis currently involves an algorithm combining pretest probability, D-dimer testing, and compression ultra sonography. This will guide further investigations if necessary. Prophylaxis is both mechanical and pharmacological. The goals of treatment are to prevent extension of thrombi, recurrence of thrombi, pulmonary embolism and also prevention of complications.DVT is a potentially dangerous condition with risk factors. The mainstay of treatment is anticoagulant therapy. Low-molecular-weight heparin, unfractionated heparin, and vitamin K antagonists have been the treatment of choice. Currently anticoagulants specifically targeting components of the common pathway have been recommended for prophylaxis. These include Fondaparinux, a selective indirect factor Xa inhibitor and the new oral selective direct Thrombin inhibitors (Dabigatran) and selective factor Xa inhibitors (Rivaroxaban and Apixaban). Others are currently undergoing trials. Thrombolytics and vena caval filters are very rarely indicated in special circumstances.